Autogenous Dental Transplantation: Case Series - dos Santos, Mateus Veppo; Vieira Frujeri, Maria de Lourdes; Oliveira, Laura Fagundes; Oliveira, Laura Melo; Paixão, Mariana Guimarães; Santana Santos, Rita De Cássia (The Journal of Dentists, 2023)
Autogenous dental transplantation is defined as the transfer of a tooth to a recipient site of the same individual, whether it is a recently extracted site or surgically prepared bed. This procedure has proven to be a good and cost-effective alternative for replacing teeth with indications for extraction. Depending on the case, it is possible to maintain the vitality of the tooth and the periodontal ligament, ensuring proprioception and physiological dental mobility. The aim of the study is to describe a series of clinical case reports of autogenous dental transplants, in addition to discussing the results obtained based on current literature. The study features with a series of autogenous dental transplant cases conducted at Euro American University Center, where the indication for such a procedure was the extensive coronal destruction of the first molars in young patients. The surgeries were performed in atraumatic manner using a single-stage technique and semi-rigid splinting with occlusive sutures using 4-0 nylon thread. The results demonstrate significant success in the postoperative period, with the absence of symptoms and maintenance of pulp vitality and periodontal ligament. Based on the studies and case reports, it was observed that transplantation remains a safe and economically viable alternative for the replacement of prematurely lost teeth, within its indications and limitations.